Ultrasonic inspection of flooded mineshafts for stability monitoring. Issue 3 (3rd July 2019) - Bedford, Michael D.; Gibson, David; Coggan, John; Siever, Klaus; Wrana, Aleksander; Sobczak, Dagmara; Álvarez, Olaya; Satterley, Chris
ABSTRACT: Inspecting abandoned mine shafts is critical in ensuring their safety through early identification of signs of deterioration. Since the common inspection methods of CCTV and LiDAR are not very effective underwater, two modules have been designed for inspecting the linings of flooded, abandoned mine shafts. Using sonar technology, they allow the early stages of degradation to the lining to be detected which – since this could be indicative of imminent collapse – provides protection against the consequential risk to property and human life. Detailed measurements of several shafts' cross-sections have been recorded using profiling and imaging sonar technology. Although imaging sonar provides very different results in the confined and reverberant environment of a mine shaft, compared to its more common environment of a seabed, it was shown that when combined with the profiling sonar, it allows shafts to be surveyed in a shorter period of time and improves the reliability of the profiling function.